2022
DOI: 10.1302/0301-620x.104b11.bjj-2022-0574.r1
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the influence of modifiable patient-related factors on complication rates after adult spinal deformity surgery

Abstract: Aims Postoperative complication rates remain relatively high after adult spinal deformity (ASD) surgery. The extent to which modifiable patient-related factors influence complication rates in patients with ASD has not been effectively evaluated. The aim of this retrospective cohort study was to evaluate the association between modifiable patient-related factors and complications after corrective surgery for ASD. Methods ASD patients with two-year data were included. Complications were categorized as follows: a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 41 publications
0
3
0
Order By: Relevance
“…2 Fractures caused by osteoporosis are becoming increasingly common in females over the age of 55 years, leading to a large number of fracture-related diseases and increased mortality and medical costs. [3][4][5][6][7] The pathogenesis of osteoporosis involves complex signalling pathway regulation and protein modification; however, little is currently known about this process. Osteoporosis is mainly caused by osteoclast-mediated bone resorption.…”
Section: Introductionmentioning
confidence: 99%
“…2 Fractures caused by osteoporosis are becoming increasingly common in females over the age of 55 years, leading to a large number of fracture-related diseases and increased mortality and medical costs. [3][4][5][6][7] The pathogenesis of osteoporosis involves complex signalling pathway regulation and protein modification; however, little is currently known about this process. Osteoporosis is mainly caused by osteoclast-mediated bone resorption.…”
Section: Introductionmentioning
confidence: 99%
“…However, relatively high rates of poor bone quality have been reported in younger surgical spine patients [ [90] , [91] , [92] ]. Williamson et al [ 93 ] further demonstrated the clinical significance of this, showing that in patients under 65 with minimal deformity, osteoporosis was the most significant risk factor for major mechanical (33% vs. 7% without osteoporosis, p=.025; OR 5.9, p=.048) and major radiological (29% vs. 6%, p=.001; OR 7, p=.003) complications, trends not observed in their overall cohort. Moreover, our review suggests that patients with poor bony strength despite a non-osteoporotic BMD may also be at increased risk for mechanical complications.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies did not show the difference in age between groups [ 10 , 12 , 13 ], but the current meta-analysis detected that the loosening group was older than the control group. Elderly patients frequently have severe osteopenia and paravertebral muscle degeneration, which may increase the screw loosening rate [ 22 , 23 ]. Previously, Iijima et al [ 13 ] reported a higher obesity rate in the S2AI screw loosening group.…”
Section: Discussionmentioning
confidence: 99%